Building Sustainable Branding in the Hospitality & Tourism Industry: Integrating Corporate Identity, Social Responsibility, and Reputation - Suyamto Suyamto; Dian Deliana; Sujatmiko Sujatmiko (International Journal of Management Science and Information Technology, 2025)
This study explores the association of corporate identity, social responsibility, and reputation in the development of successful sustainable branding in the hospitality and tourism sector of Indonesia. We used mixed methods applying quantitative analysis and collect the data in a systematic arrangement from various big cities considering the tourists. A 1,219-panel sample of small to medium-sized businesses were surveyed. Our conclusions are that many companies have successfully created an organizational identity internally through the alignment of communicated values and management's daily actions. Social and environmental obligations are demonstrated in supporting local communities, energy conservation and preservation of the culture. There are still a few that are not officially documented, but everybody knows these to be part of the company’s overarching strategy. Corporate image, from a job evaluation standpoint, is supported by open communication, listening to feedback and a digital presence. The results of the path analysis support the effect of corporate identity on social action and reputational perception. And the connection between social responsibility and reputation is robust. Relationships between variables remain constant, while regional comparisons reveal diverse trends. Bali is the most advanced when it comes to identity and reputation, with Lombok and Labuan Bajo concentrating more on community engagement. Interviews and focus groups reveal that involvement of the staff in social activities also contributes to sense of ownership and pride in the workplace. The fusion of values, participation and regular behavior author the maintenance of public trust in an industry so based on perception.